El vacío como espacio integrador: estudio urbano de la av. Unidad Nacional entre la Av. Carlos Zambrano y la Av. la Prensa - Asitimbay Velata, Cristhian Edgar (2018)
Since the beginning, Riobamba has had wide public spaces and urban exes, helping to decentralize is historic center. Lately, the city has experienced a faster spatial wide; this has converted the Unidad Nacional Avenue in an exclusive use of cars, taking out the public spaces of the Train and of the Puruhá, generating an urban empty. Because of the characteristics, potentials and particular aspects of the avenue and the public spaces, it is important to elaborate a diagnostic and a descriptive analysis that will be developed by collecting real information about the central problem that causes it in order to formulate a proposal to get a better reactivation of these spaces; to convert the urban empty space in a connector space, to give a better city image and life quality for citizens. The city study presents a reactivation of a very important urban exe, creating a nice / good urban image based in a redesign and union of the Train park and the Puruhá, giving urban condition of the public spaces which have been absent until now in the area.